El uso político del baile en el Clásico maya: el baile de K’awiil - García Barrios, Ana; Valencia Rivera, Rogelio (Revista Española de Antropología Americana, 2007)
During the Classic Period, ceremonial dancing was used as a public mechanism to evidence power relationships among the Maya. This was specially notorious in a very specific dance performed during the celebrations related to the change of government; in which the king dances holding a K’awiil sceptre. This dance was represented in public inscriptions when the right of the king to govern was not very clear, ending up as a consolidation mechanism employed in some Maya sites with a Calakmul’s filiation